New Hybrid Intelligent Systems for Diagnosis and Risk Evaluation of Arterial Hypertension - Melin, Patricia; Prado-Arechiga, German; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
In this book, a new approach for diagnosis and risk evaluation of ar-terial hypertension is introduced. The new approach was implement-ed as a hybrid intelligent system combining modular neural net-works and fuzzy systems. The different responses of the hybrid system are combined using fuzzy logic. Finally, two genetic algo-rithms are used to perform the optimization of the modular neural networks parameters and fuzzy inference system parameters. The experimental results obtained using the proposed method on real pa-tient data show that when the optimization is used, the results can be better than without optimization. This book is intended to be a refer-ence for scientists and physicians interested in applying soft compu-ting techniques, such as neural networks, fuzzy logic and genetic algorithms, in medical diagnosis, but also in general to classification and pattern recognition and similar problems.
From the Content: Introduction -- Fuzzy Logic for Arterial Hypertension Classification -- Design of a Neuro Design of a Neuro Design of Arterial Hypertension.
Keywords: Computational intelligence; Biomedical engineering; Medical informatics; Computational Intelligence; Biomedical Engineering and Bioengineering; Health Informatics